An approximate solution of the affine-quadratic control problem based on the concept of optimal damping - Veremey, Evgeny I. (Zielona Góra: Uniwersytet Zielonogórski)
The paper is devoted to a particular case of the nonlinear and nonautonomous control law design problem based on the application of the optimization approach. Close attention is paid to the controlled plants, which are presented by affine-control mathematical models characterized by integral quadratic functionals. The proposed approach to controller design is based on the optimal damping concept firstly developed by V.I. Zubov in the early 1960s. A modern interpretation of this concept allows us to construct effective numerical procedures of control law synthesis initially oriented to practical implementation.
Keywords: feedback; stability; damping control; functional; opt